Sistema para análise biomecânica de nadadores SABIO - Persona, Karina Lorenti (2006)
The aim of this work was the development of a system based on images acquisition that assists in the training and in the biomechanics analysis of the athletes, specifically, of swimmers. The analysis focused at identification and the quantification of the biomechanical factors that can improve the performance of swimmers, because the optimization of small values can mean the victory in swimming. For the biomechanics evaluation is necessary to know some parameters of a swimmer, such as partial speed and average speed of the swim, stroke frequency and length, rhythm of swim, mensurement of articular angles, among others. So that these data represent faithfully athlete's values, without limiting their actions with equipment coupled to then, the system denominated SABIO is divided into hardware and software. The hardware is composite for several elements like as video cameras, pool signs and system of visual stimulus and it has the function of capture images of the swim in the plan sagital of the athlete, defining interest points in environment and in the swimming pool and to dictate the test rhythm. The software fulfills the calculations of the swim parameters and the biomechanics analysis of the swimmers. They were accomplished several tests, with athletes of distinct modalities in all development stages of the system, for adjustment of the materials involved in the hardware. For validation of the SABIO, it was studied the kinematics aspect of the movements of an athlete. The results obtained by the system ware expected and allowed to analyze the wished factors.